2003
DOI: 10.1001/jama.290.4.465
|View full text |Cite|
|
Sign up to set email alerts
|

Breast Cancer Following Radiotherapy and Chemotherapy Among Young Women With Hodgkin Disease

Abstract: REATMENT OF HODGKIN DISease (HD) represents one of the major medical successes of the 20th century. Fifty years ago, the typical patient survived only a few years, 1 whereas the current 5-year relative survival rate is 85%. 2 In the United States alone, approximately 120000 survivors of HD 2 are at risk for the serious late sequelae of curative therapies, including the occurrence of new primary cancers. 3,4 Second malignant neoplasms are now the leading cause of death in longterm survivors of HD, 5,6 with brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
484
0
9

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 601 publications
(518 citation statements)
references
References 53 publications
25
484
0
9
Order By: Relevance
“…One (Travis et al, 2003) was a matched case-control study within a cohort of 3817 female 1-year survivors of Hodgkin disease diagnosed at age 30 years or younger, between January 1, 1965, and December 31, 1994, and within 6 population-based cancer registries. Record-linkage techniques were used to identify women who developed a second primary breast cancer.…”
Section: Data Sets and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…One (Travis et al, 2003) was a matched case-control study within a cohort of 3817 female 1-year survivors of Hodgkin disease diagnosed at age 30 years or younger, between January 1, 1965, and December 31, 1994, and within 6 population-based cancer registries. Record-linkage techniques were used to identify women who developed a second primary breast cancer.…”
Section: Data Sets and Analysismentioning
confidence: 99%
“…The data sets used, set 1 (Travis et al, 2003) and set 2 ( van Leeuwen et al, 2003), are described in the Methods section. The figure shows predictions, all of which use K=25 acute dosefractions, starting on a Monday and continuing daily except for Saturdays and Sundays.…”
Section: Fig 5 Comparing Different Models With Data On Second Breasmentioning
confidence: 99%
“…Reaching menopause before age 36 years was associated with a greatly reduced risk of breast cancer (RR 0.06, 95% CI 0.01 -0.45) and risk increased steeply with number of premenopausal years after treatment: relative risks were 0.15, 0.24 and 0.91 for o5, 5 -14, and X15 premenopausal years, respectively. Travis et al (2003) found that breast cancer risk decreased significantly (P ¼ 0.003) with increasing number of alkylating agent cycles and decreased, although the trend was not significant, with younger age at menopause. Thus ovarian hormones may be critical to carcinogenesis after radiation initiation.…”
mentioning
confidence: 95%
“…Analyses of patients treated with both chemotherapy and radiotherapy have in several studies (Gervais-Fagnou et al, 1999;Swerdlow et al, 2000;van Leeuwen et al, 2000Travis et al, 2003) but not all (Hancock et al, 1993;Aisenberg et al, 1997) suggested a reduced risk compared with that after radiotherapy alone. In the British cohort, the relative risk for patients treated at less than 25 years of age was 14.4 after radiotherapy alone and 4.6 after radiotherapy plus chemotherapy (Swerdlow et al, 2000).…”
mentioning
confidence: 99%
“…There is significant evidence, derived from diverse populations, that ionising radiation can cause breast cancer. Some examples are patients who received therapeutic radiation to the chest early in life for Hodgkin's disease (HD), patients who were treated with radiation for mastitis and other benign breast diseases, patients who received thymic irradiation, patients who underwent frequent fluoroscopies for pulmonary disease, and atomic bomb survivors (Behrens et al, 2000;Clemons et al, 2000;Gaffney et al, 2001;Land et al, 2003;Travis et al, 2003). Among these, the best-studied group are women who developed breast cancer after treatment for HD.…”
mentioning
confidence: 99%